2001
DOI: 10.1146/annurev.physiol.63.1.259
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanism of Oxygen Sensing

Abstract: O2 sensing is a fundamental biological process necessary for adaptation of living organisms to variable habitats and physiological situations. Cellular responses to hypoxia can be acute or chronic. Acute responses rely mainly on O2-regulated ion channels, which mediate adaptive changes in cell excitability, contractility, and secretory activity. Chronic responses depend on the modulation of hypoxia-inducible transcription factors, which determine the expression of numerous genes encoding enzymes, transporters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
427
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 508 publications
(440 citation statements)
references
References 138 publications
9
427
0
4
Order By: Relevance
“…Two major classes of hypoxia signaling pathways are activated: fast (seconds to minutes) responses mediated through O 2 -sensitive ion channels and slow (hours to days) responses that involve transcriptional activation of hypoxia-inducible genes (Lopez-Barneo et al, 2001). In mammalian forebrain neurons, for example, fast responses to hypoxia lead to hyperpolarization by activating K Ca and K ATP currents and reducing voltage-gated Na currents (Lopez-Barneo et al, 2001). The best characterized slow responses are those orchestrated through the basic helix-loop-helix Per-Arnt-Sim transcription factor, HIF-1.…”
Section: Discussionmentioning
confidence: 99%
“…Two major classes of hypoxia signaling pathways are activated: fast (seconds to minutes) responses mediated through O 2 -sensitive ion channels and slow (hours to days) responses that involve transcriptional activation of hypoxia-inducible genes (Lopez-Barneo et al, 2001). In mammalian forebrain neurons, for example, fast responses to hypoxia lead to hyperpolarization by activating K Ca and K ATP currents and reducing voltage-gated Na currents (Lopez-Barneo et al, 2001). The best characterized slow responses are those orchestrated through the basic helix-loop-helix Per-Arnt-Sim transcription factor, HIF-1.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that it occurs at the transcriptional level and is mimicked by DMOG and cobalt, inhibitors of prolyl hydroxylases. 24,[35][36][37] Hypoxic regulation of the ␤ 1 gene is independent of membrane depolarization and extracellular Ca 2ϩ influx. The maxi-K ␤ 1 -subunit mRNA expression is also decreased by the application of hydrogen peroxide, an observation fully compatible with the notion that production of reactive oxygen species in mitochondria during hypoxia is required for effective inhibition of prolyl hydroxylases and subsequent stabilization of Hif proteins.…”
Section: Hif-2␣-dependent Hypoxic Downregulation Of the ␤ 1 -Subunit mentioning
confidence: 99%
“…From an intuitive standpoint, one might assume that ROS levels drop during hypoxia since ROS require O 2 as a substrate for their production and several studies support this prediction. For instance, it has been shown that endothelial cell plasma membranes release less extracellular H 2 O 2 under hypoxia compared to normoxia [64,65]. In addition, perinuclear endoplasmic reticulum (ER) generation of OH, presumably derived from the "Fenton reaction" of H 2 O 2 with transition metals, is higher under normoxic conditions compared to hypoxia [66].…”
Section: Ros and Hypoxiamentioning
confidence: 99%